99mTc-Besilesomab-SPECT/CT in Infectious Endocarditis: Upgrade of a Forgotten Method? - Bouter, Caroline; Meller, Birgit; Sahlmann, Carsten O.; Meller, Johannes (Frontiers in Medicine, 2019)
Infective endocarditis displays a serious condition with high mortality rates. Establishing a reliable diagnosis can be challenging. This study evaluates granulocyte imaging with 99mTc-Besilesomab-SPECT/CT in order to determine the clinical value of the method and its possible redefinition through the addition of hybrid imaging. The study comprises 26 consecutive patients with suspected infectious endocarditis or prosthetic valve infection that underwent 99mTc-Besilesomab-SPECT/CT in our facility between December 2016 and September 2018. 99mTc-Besilesomab-SPECT/CT images were reviewed by two independent and blinded observers and results were evaluated by transesophageal echocardiography (TEE) and blood culture results as well as by pathological, bacteriological and clinical findings. Target-to-Background-Ratios were calculated for semi-quantitative analysis. 13/26 patients were in a post-surgical stage. 99mTc-Besilesomab-SPECT/CT was positive in 6 cases. All 6 cases were true positive confirmed by pathological or clinical findings according to the modified Duke Criteria for infective endocarditis. Remaining 19/26 cases were true negative. Target-to-Background ratios were significantly higher in patients that were visually scored positive compared to negative cases. Inter-observer agreement was very good of deciding whether a scan was positive or negative. Sensitivity of 99mTc-Besilesomab-SPECT/CT was 86% to 100% and specificity was 100%. 99mTc-Besilesomab-SPECT/CT is a useful imaging method for the diagnosis of endocarditis, especially in difficult cases with prosthetic valves or cardiac devices and inconclusive findings in echocardiography. The added value of SPECT/CT was mainly finding and localizing increased uptake at a certain valve, prosthesis or device cable.